The repercussions of Sufi thoughts in the contemporary Qur’anic Interpretation to Sustainable Development in Indonesia - Suadi Sa`ad; David Ming; Agus Sukirno; Yusuf Rahman; Abdul Kadir Riyadi (Pharos Journal of Theology)
The repercussions of Sufi thought on contemporary Qur'anic interpretation in Indonesia align with several Sustainable Development Goals (SDGs) by fostering values such as inclusivity, environmental stewardship, and social justice. Sufi-inspired interpretations often emphasize compassion, charity (zakat), and equitable resource distribution, which directly contribute to poverty reduction and social equity. Sufi teachings promote spiritual equality between men and women, which has influenced Qur'anic interpretations advocating for gender justice. Sufi thought emphasizes harmony with nature, reflecting the Qur'anic mandate to maintain ecological balance. Efforts to harmonize these perspectives remain crucial for maximizing the role of Islamic teachings in achieving sustainable development goals. Indonesia has become a dynamic arena for the struggle of religious thoughts. Among the most exciting aspects of this are the repercussions of Sufi thoughts in interpreting the Qur’an. In the cultural and historical context of the region, the connection between the Sufi view that emphasizes to develop inner spirituality and Qur’anic interpretation has been deeply rooted. Analyzing the data to identify patterns, correlations, or trends and from the findings concluding the overall repercussion of Sufi thoughts in contemporary Qur’anic interpretation to sustainable develop in Indonesia. Islam is the basis of Sufism and it accepts that all of creation has benefits and must be sustained, and glorify Allah. All creatures glorify Allah and this is considered to be the basis of truth. This study concludes that the repercussions of Sufi thoughts on interpretation to sustainably develop Indonesia can be classified as "moderate". The conclusion is based on the findings that several interpretations to sustainable development, especially social cohesion, are often adopted in the thoughts of prominent Sufi figures and used as a basis for interpreting Qur’anic verses.